ANALYSIS OF THE INFLUENCE OF MECHANICAL PROCESSING ON STRUCTURAL, MECHANICAL, PHYSICAL AND CHEMICAL PROPERTIES OF RAW MEAT - Donets A.P.; Pokintelitsa N.I. (Техника и технология пищевых производств)
The article reveals the results of experiments aimed at determining the influence of raw meat mechanical processing and multifunctional brines, which consist of connective tissue proteins with further massaging, on the structural, mechanical, physical, chemical and technological properties of the finished meat products. Beef pickling intensity and improvement of finished product quality are based on three main points: enhancing of meat softness as a result of tissue mechanical destruction, activation of the uniform distribution of salt brines within meat pieces, the artificial injection and uniform functional ingredients redistribution. Preparation of multifunctional blends for beef pickling, which would combine the best available ingredients and provide the optimal balance between functionality, efficiency and quality, is an important task which allows to expand the product range and stabilize the quality of the finished products. The research results indicate the influence of multicomponent brines on the change in pH and water- holding capacity of raw meat. Developed recipes of brines used for injection allow to achieve salty beef DFD ham products with more tender and plastic structure with the required structural-mechanical quality indicator. Presented researches series is dedicated to the laws priority determining of the multicomponent brines influence on the raw meat pH change, and confirmation based on this, theproposed hypotheses on the possible regulation of the main physico-chemical indicators of source of the meat raw materials and finished products. Research has shown that the higher the level of raw meat injection, the higher is the ductility of the samples, indicating the influence of not only the brine quantity, but also its qualitative composition. The prototypes organoleptic evaluation showed that the ham products, made from the corresponding samples of beef, have satisfactory organoleptic properties and do not differ significantly from samples with a lower percentage of brine for injection.